Teacher Education in Nepal and Denmark: A Comparative Study - Lamichhane, Sujana (The EFFORTS, Journal of Education and Research, 2024)
This article investigated the teacher education policies, practices, and their influence on teaching learning activities in Nepal and Denmark. The study presents a comparison of the teacher education system and practices between Nepal and Denmark. The study is based on the literature reviewed in the case of Denmark whereas in the case of Nepal, it is based on the data obtained from the various stakeholders. The study adopts an interpretive approach under qualitative research design which includes in-depth interviews with university teachers, Center for Education and Human Resource Development (CEHRD) executive and focus group discussions with school teachers. Findings indicate that teacher education in Nepal started far later than in Denmark and shares some similarities with distinct differences in policy stability. Enrollment in teacher education courses is decreasing due to unemployment issues which may affect the quality of education in future. Furthermore, the results indicate that new demand-based approaches to teacher education, capacity enhancement of training centers, effective monitoring mechanisms, qualified teacher educators, and efficient ICT integration are the major aspects of needed improvements.